2016
DOI: 10.1016/j.actamat.2016.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent dispersoid stability in ion-irradiated ferritic-martensitic dual-phase oxide-dispersion-strengthened alloy: Coherent interfaces vs. incoherent interfaces

Abstract: a b s t r a c tIn this study, the microstructure of a 12Cr ferritic-martensitic oxide-dispersion-strengthened (ODS) alloy is studied before and after Fe ion irradiation up to 200 peak displacements per atom (dpa). Irradiation temperature ranges from 325 to 625 C. Before irradiation, both coherent and incoherent dispersoids exist in the matrix. In response to irradiation, the mean sizes of dispersoids in both the ferrite and tempered martensite phases change to equilibrium values that increase with irradiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 73 publications
4
24
0
Order By: Relevance
“…This explains the changes of the density and size of oxides before and after irradiation in coarse grains of COS-2. The evolution of oxide particles in COS-2 is similar to a previous work conducted by Chen27. Chen and his colleagues systematically studied the coherency of the dispersoids before and after irradiation.…”
Section: Discussionsupporting
confidence: 74%
“…This explains the changes of the density and size of oxides before and after irradiation in coarse grains of COS-2. The evolution of oxide particles in COS-2 is similar to a previous work conducted by Chen27. Chen and his colleagues systematically studied the coherency of the dispersoids before and after irradiation.…”
Section: Discussionsupporting
confidence: 74%
“…Finally, it is observed that upon both Fe 2+ and proton irradiation, the average sizes of the oxide nanoclusters appear to asymptotically approach steady-states at doses >3 dpa, consistent with previous modeling [57,74,79] and experimental [5,79,84,107,206] efforts.…”
Section: Ods Oxidessupporting
confidence: 72%
“…Using high resolution transmission electron microscopy (HRTEM), several studies have found oxides to generally be coherent with the matrix [69,79,88,96,128]. Observations in literature also suggest that coherency may be closely related to the size of clusters, with smaller oxides trending towards non-stoichiometric chemistry with Y:Ti ratio ~0.50 [9,13], while larger oxides trend towards a Y:Ti ~1.3 [9,13] with a pyrochlore Y2Ti2O7 or orthorhombic Y2TiO5 structure [124,[130][131][132][133][134].…”
Section: Crystal Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Size changes are the most widely reported factor describing the irradiation evolution of NPs, and it is of interest to understand these size changes as a function of irradiation dose. Only a few studies have carried out NP size measurements over a range of doses (with all other irradiation parameters fixed); these results are represented in Chen, et al [8] both observe decreasing NP size with increasing dose, with a steady-state reached between 50 and 150 dpa. But the similarities end there.…”
Section: Size Number Density and Volume Fractionmentioning
confidence: 99%